In vitro antioxidant activity of the individual herbs of DIA-2, a herbal mixture containing standardized extracts of Allium sativum and Lagerstroemia speciosa - Krishnan Selvarajan Kesavanarayanan & , Subramanian Kavimani, Duvuru Prathiba (Journal of Applied Pharmaceutical Science, 2015)
Hyperglycemia induced oxidative stress is one of the main mechanism involved in the pathogenesis of diabetic complications. Use of antioxidants as an adjuvant therapeutic approach in diabetes could prevent or delay the progression of oxidative stress induced diabetic complications. Many herbal drugs possess multiple pharmacological actions like anti-hyperglycemic, anti-obesity and anti-oxidant properties etc., which could act through multiple pathways and may offer beneficial effect in the management of multi-factorial diseases such as diabetes. Development of herbal formulation with ingredients having multiple actions could be a potential approach for improving therapeutic efficacy. We here report the free radical scavenging activity of a herbal mixture, DIA-2 and its individual herbs. DIA-2, a herbal formulation containing fixed combination of standardized aqueous extracts of Allium sativum (ASE) bulbs and Lagerstroemia speciosa (LSE) leaves. The present study was undertaken to investigate whether a combination of ASE and LSE shows a synergistic antioxidant effect than its individual herbs. In vitro antioxidant activity for individual herbs and DIA-2 was determined by DPPH radical scavenging, nitric oxide scavenging assay, total antioxidant capacity, reducing power assay and ABTS radical scavenging methods respectively. Our results suggest that DIA-2 could synergistically enhance the antioxidant activity and could be attributed due to the synergistic actions of the individual ingredients. The data obtained suggests the combined use of ASE and LSE as active ingredients in the development of antidiabetic herbal formulation, synergizing its therapeutic value in treating hyperglycemia and associated oxidative stress.
Keywords: DIA-2, Allium sativum, Lagerstroemia speciosa, Diabetes mellitus, Antioxidant, Oxidative stress.